Pengaruh Pembelajaran Blended Learning Terhadap Peningkatan Fleksibilitas Togok Dalam Pembelajaran Senam Lanjutan - Firdaus Hendry Prabowo Yudho (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
This research aims to uncover the effects of blended learning in advanced gymnastic learning activities that are carried out for one semester with a total of 8 online sessions and 8 offline sessions quantitatively. The method used in this study used quasi-experiments with a sample of 31 people. The research data were obtained with sit and reach test instruments to be analyzed using quantitative analysis, other non-parametric Wilcoxon test methods, with the results of the study conclusions there was no significant change between the results of the sit and reach tests obtained from the blended learning process in advanced gymnastic learning.